(untitled) (The Agriculturists, 2017)
A field experiment was conducted at the central nursery of tea extension center of Bangladesh Tea Board in Bandarban during September to November, 2015 to determine the precise concentration of Indole Butyric Acid (IBA) on propagation through stem cuttings of tea. The experiment was laid out in a randomized block design with four treatments of IBA concentrations: 0 ppm (Control), 2000 ppm, 4000 ppm and 6000 ppm and each treatment was replicated four times. Basal part of tea (BT-2 variety) cuttings were dipped in different IBA concentrations for five seconds. Then these cuttings were dibbled into prepared soil mixture as rooting media. Cuttings were exposed to the rooting media for 90 days and then they all were removed carefully to assess the variation of establishment of cuttings. IBA treated cuttings showed better effect on the rooting rate, root length, root number, shoot length and survival rate compared to the control. It was noted that cuttings treated with 4000 ppm IBA produced the highest rooting rate 79.85%, the highest survival rate 57.60% and the highest root length of 4.85 cm followed by treatment 6000 ppm IBA. In case of all parameters, effects of the treatments 4000 ppm and 6000 ppm of IBA were statistically similar. Positive and strong correlation was observed both in rooting rate versus survival rate and root length versus shoot length in IBA treated cuttings. Thus, IBA at 4000 ppm concentration was recommended for establishment of stem cuttings of tea (BT-2 variety) in the nursery. The Agriculturists 2016; 14(2) 124-129